Metode merjenja mišične kakovosti za razvrščanje sarkopenije - Puš, Katarina (Šport (Ljubljana), 2022)
Muscle quality is a term that refers to micro- and macroscopic changes in muscle architecture and composition and to muscle function delivered per unit of muscle mass. Therefore, a lot of different measurement methods are in use. Muscle quality can be assesed through two components: neuromuscular and morphological. Latter is usually assessed by imaging techniques, neuromuscular component uses ratios between muscle strength per muscle mass unit or volume. Muscle quality is an important parameter of sarcopenia definition and diagnosis, thus we have focused on muscle quality assessment methods for sarcopenia diagnosis.
Keywords: definicija; merjenje; Mišice; Mišično-skeletni sistem; sarkopenija